El proceso inmediato en el marco de la imparcialidad - Gerònimo Lòpez, Marìa Angélica (2018)
Keywords: Immediate process, judicial impartiality (subjective dimension and objective dimension) and decided theme. This thesis has as its central axis the study of the immediate process with the purpose of determining if the single hearing of immediate judgment transgresses the judicial impartiality, since it is composed by two phases in charge of a Judge of Judgment that will solve the requests formulated by The parties will admit the evidence that will be submitted to debate, resolve the issues raised in accordance with Article 350 of the Criminal Procedure Code of 2004 and issue a judgment. In the present work, the immediate process has been analyzed within the framework of judicial impartiality; the tendency of the sentences of sight issued in the period from January to October by the First Criminal Chamber of Appeals of Trujillo that declare the nullity or revoke the sentences issued in the immediate judgment. From this, it was agreed that impartiality has a subjective dimension and an objective dimension, verifying that the objective dimension identifies a judge model that eliminates from its image any shadow of disconnection with the parties or the object of the process that can justify appearance of partiality and, in turn, ensures that the Judge approaches thema decidendi without having taken a position in relation to him. In the same way, warning that the plenary agreement 6-2009 determined that the evidentiary admissibility, proper of the control of accusation, implies a formal control and a substantial control of the accusation; that substantial control directs the Magistrate to define a certain position; and, that the tendency was to approve the resolutions that were raised in consultation and declared, in accordance with Article 53, paragraph 1, letter d of the criminal procedure code, the inhibition of the trial judges who had intervened in the common proceedings as judges. of preparatory research and had acted according to their competences; After the above, it was determined that the single hearing of immediate judgment violates the objective impartiality of the judge; so that a proposal for a normative amendment was made that guarantees it fully and is compatible with the regular Peruvian criminal process.